Research and Experiment on Separation Method of Different Electromagnetic Field Components Measured by Tilting Coil - TIAN Yuanshi; ZHU Jun; DIE Yong; YANG Shansen; YANG Ting; LIU Xiao (Cejing jishu)
Tilt coil is one of the commonly used antenna structures of azimuthal electromagnetic wave logging while drilling tools, which is widely used in Schlumberger, Halliburton and such instruments developed in China National Offshore Oil Corporation and China National Logging Corporation. The measured signal of tilt coil is the superposition of two electromagnetic signals of different components. It is often necessary to extract separate electromagnetic components from the mixed signal for further analysis during data processing and inversion. At present, such logging tools have been developed at home and abroad, but the research on the extraction method of electromagnetic field components is very few. This paper presents a method for extracting signals of different electromagnetic field components measured by inclined coil. The antenna system structure of measuring while drilling electromagnetic wave boundary detection instruments including inclined coils and the electromagnetic field components contained in the measured signals are summarized. The feasibility of the method is verified by physical simulation and numerical simulation, and the method of extracting single component signals through Discrete Fourier Transform is proposed. The feasibility of the method is verified by simulation examples. The simulation results show that the method described can separate electromagnetic field signals of individual components, and the directional characteristics of the separated electromagnetic field signals are consistent with the numerical calculation results, which provides a theoretical basis for the application of instrument engineering.